Strength in power events: Theory and practice - Marques, M. A. C. (Journal of Human Sport & Exercise, 2010)
Over the last 30 years, strength and power training has been a major issue for, coaches, athletes and researchers. Unfortunately, despite the increasing professionalization of coaches and athletes, there is little research data concerning performance in top athletes. In fact, experimental studies in high level athletes are very difficult to put into practice for many reasons. However, such considerations ought not to detract from the necessity and importance of this type of research in strength and power events. Many experiments demonstrated that a specific strength training program can improve athletes' maximal force and power production, reduce the incidence of injury, and contribute to faster injury recovery times, thereby minimizing the number of missed practice sessions and competitions. But, to our best knowledge, there is no apparent consensus on the appropriate method of strength and power training to enhance performance, especially in typically power sports. Therefore, the aim of this paper was to ask practical questions: How much strength should be employed? Is maximum strength the main issue? Is power and rate of force development the key? Is periodization of major importance?